OP0106 Change in Bone Mineral Density with High-Dose Prednisone in Patients with Rheumatoid Arthritis. (15th July 2016) - Rasch, L.; van Tuyl, L.; Kremer, M.; Bultink, I.; Boers, M.; Lems, W.
Abstract : Background: Recently, we showed that treatment with COBRA-light therapy including prednisone with initially 30 mg/day, was as effective as the original COBRA scheme, with initially 60 mg/day [1, 2], in the treatment of rheumatoid arthritis (RA). Since high-dose glucocorticoids are associated with bone loss and vertebral and nonvertebral fractures, we investigated the differences in bone mineral density (BMD) after one year of treatment in both arms. Objectives: To compare 1-year changes in BMD (lumbar spine [L1-L4], total hip, and femoral neck) between the treatment groups. Methods: An open-label, randomised controlled, non-inferiority trial of patients with active, newly diagnosed RA following a treat-to-target protocol. Results: BMD data were determined in 144 out of 164 included RA patients, all randomized to either COBRA (n=71) or COBRA-light (n=73) therapy. Overall bone loss was very limited, and no significant difference in change in BMD between COBRA and COBRA-light was found at any site ( Table 1 ). However, in secondary analyses, COBRA-light showed a significant decrease in BMD in the lumbar spine and total hip after 52 weeks, whereas the femoral neck and the COBRA group did not. Conclusions: During the trial, overall bone loss was very limited and not significantly different between the treatments. These findings strengthen the hypothesis that positive effects associated with the large reduction in disease activity as a result of combination therapy and tight control treatment counteract the negative effects of (high-dose) prednisone on bone. References: Den Uyl D, et al. Ann Rheum Dis 2014; Ter Wee MM, et al. Ann Rheum Dis 2015 Disclosure of Interest: L. Rasch: None declared, L. van Tuyl: None declared, M. Kremer: None declared, I. Bultink: None declared, M. Boers: None declared, W. Lems Grant/research support from: This research was performed within the framework of project T1–106 of the Dutch Top Institute Pharma, and was additionally funded by an unrestricted grant from Pfizer.